Consensus statement on the management of patients with asymptomatic hyperuricemia in general medical practice - O. M. Drapkina; V. I. Mazurov; A. I. Martynov; E. L. Nasonov; S. A. Saiganov; A. M. Lila; R. A. Bashkinov; I. N. Bobkova; Ch. T. Baimukhamedov; I. Z. Gaidukova; N. I. Guseinov; D. V. Duplyakov; et al. (Кардиоваскулярная терапия и профилактика)
.